2023
DOI: 10.3390/molecules28145415
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols and Neurodegenerative Diseases: Potential Effects and Mechanisms of Neuroprotection

Raziel Alejandro Arias-Sánchez,
Luz Torner,
Bertha Fenton Navarro

Abstract: The increase in people’s longevity has, consequently, led to more brain involvement and neurodegenerative diseases, which can become complicated and lead to chronic degenerative diseases, thereby presenting greater public health problems. Medicinal plants have been used since ancient times and contain high concentrations of molecules, including polyphenols. It has been proven that polyphenols, which are present in various natural sources can provide curative effects against various diseases and brain disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 88 publications
0
19
0
Order By: Relevance
“…They have been perceived in several reports as anti-neuroinflammatory by blocking the release of cytokines (TNF-α and IL-1β), inhibiting NF-κB expression, and reducing intracellular Aβ and the hyperphosphorylation of tau. 50–53 The results of the study displayed that the fruit extract of K. elegans has a more potent anti-inflammatory effect than the leaf extract in a mice model of AD. The fruit extract reduced TNF-α, NF-κB, and IL-1β levels more than the leaf extract, which are all markers of inflammation and neurodegeneration in AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been perceived in several reports as anti-neuroinflammatory by blocking the release of cytokines (TNF-α and IL-1β), inhibiting NF-κB expression, and reducing intracellular Aβ and the hyperphosphorylation of tau. 50–53 The results of the study displayed that the fruit extract of K. elegans has a more potent anti-inflammatory effect than the leaf extract in a mice model of AD. The fruit extract reduced TNF-α, NF-κB, and IL-1β levels more than the leaf extract, which are all markers of inflammation and neurodegeneration in AD.…”
Section: Discussionmentioning
confidence: 99%
“…48 Several studies evaluated the biological activities of flavonoids as neuronal antioxidants, exhibiting anti-amyloidogenic and anti-inflammatory potential and neuroprotection and improving cognition. 50–55 K. elegans leaves and fruits are rich in flavonoids, which have potential against AD by regulating several important physiological responses. Quercetin, catechin-3-gallate, apigenin, apigenin hexoside, kaempferol and luteolin are detected in KEL and KEF.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols can delay oxidative reactions in cells by rapidly donating protons to radicals or by forming complexes with pro-oxidant metals. Furthermore, polyphenols can interact with receptors or enzymes in signal translation, promoting an antioxidant condition [ 10 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, many nutraceuticals and food-derived bioactive compounds, by virtue of their intrinsic properties, could have a dramatic role in reducing the risk factors for the arising of chronic neurodegenerative diseases. Focused emphasis has been given to the use of polyphenols, present in most vegetables, e.g., flavonoids, phenolic acids or curcuminoids, as therapeutic natural compounds against inflammation, neurodegeneration, and oxidative stress [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a greater number of blood vessels in the vicinity of Leydig cells is another sign of their increased activity and also a sign of improved nutrition of the Recently, it has been found that under conditions of oxidative stress due to aging, neurotrophins are oxidatively modified, thereby reducing their effectiveness [53]. On the other hand, there is evidence that polyphenols can enhance the synthesis of neurotrophic factors such as BDNF, NGF, neurotrophin 3 (NT3), and neurotrophin 4 (NT4), as well as increase their ability to bind directly to TRK-C receptors, regulating transcription, translation, proliferation, growth, and survival through pathways such as phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT), mitogen-activated protein kinase (MAPK), signal transducer, and activator of transcription 3 (STAT3), activating cAMP response elementbinding protein (CREB) [54]. There is a paucity of data in the literature on the effects of dietary polyphenols on neurotrophic factors in testes.…”
Section: Trk-c and Nt3 Immunoreactionmentioning
confidence: 99%